Резонер: Роман / Ч. Абдуллаев - Абдуллаев Чингиз (Черный квадрат, 2003)
Экземпляры: ф.5 (2003) / Инвентарный номер: 47003 / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: А 13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44